A Crisis Or Critical Development In Accounting Thought ? - Sukoharsono, Eko Ganis (Accounting Department,, 2007)
Much of debate have been raised regarding the radical development in accounting. This development provides a new perspective in conducting research into the realms of accounting practices. As opposite to the mainstream perspective,the postmodern perspective offers totality of relations (social, economic, political, and ideology) and advances the accounting researchers and practitioners to react into rational demands for useful information. Thus, it is irrationale if accounting today is said crisis theory, yet a critical development in accounting thought is much more rational words.